2015
DOI: 10.11591/.v4i1.4707
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Antioxidant Activity on The Ficus benjamina and Annona reticulata Leaves

Abstract: Antioxidants can prevent free radical formation. Natural antioxidants found in many plants, such as <em>Ficus benjamina </em>and <em>Annona reticulata</em>. The study aimed to compare the antioxidant activity of extracts and fractions of <em>Ficus benjamina </em>and <em>Annona reticulata</em> leaves against 1,1-diphenyl-2-picrilhydrazyl. The steps of this study consist of extraction, fractionation with n-hexane, ethyl acetate and water, phytochemical screening, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The percentages of inhibition for methanol extracts of C. fistula bark at concentrations of 20, 40, 60, 80, and 100 μ g/mL were 8.88, 27.84, 40.11, 58.88, and 85.82, respectively [ 19 ]. In addition, the ethanolic F. benjamina leaf extract had an inhibition percentage of 44.87 and was usually nontoxic [ 20 ]. The DPPH and ABTS assays showed that the P. dulce extract had the strongest antioxidant activity, followed by C. fistula and F. benjamina ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentages of inhibition for methanol extracts of C. fistula bark at concentrations of 20, 40, 60, 80, and 100 μ g/mL were 8.88, 27.84, 40.11, 58.88, and 85.82, respectively [ 19 ]. In addition, the ethanolic F. benjamina leaf extract had an inhibition percentage of 44.87 and was usually nontoxic [ 20 ]. The DPPH and ABTS assays showed that the P. dulce extract had the strongest antioxidant activity, followed by C. fistula and F. benjamina ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…According to the ORAC assay, which has been widely used to investigate the scavenging activities of several natural compounds, hydroxyl radicals are major active oxygen species causing lipid peroxidation and enormous biological damage [ 20 , 27 ]. The tested extracts scavenged peroxyl radicals in a concentration-dependent manner, as indicated by the inhibition of fluorescence decay.…”
Section: Resultsmentioning
confidence: 99%
“…The modified method of Molyneux (2004) was conducted [7]. A total of 1.5 ml of 40 µg/ml DPPH was added to various concentrations of 1.5 ml of vitamin C or supernatant.…”
Section: Antioxidant Activity Determinationmentioning
confidence: 99%